The Relationship Between Self Efficacy and Student Engagement in Students - Yunita Yunita (Edumaspul: Jurnal Pendidikan, 2023)
This research is a quantitative study with a cross sectional survey approach. The purpose of this study is to see the relationship between the concept of self-efficacy and student engagement. The hypothesis in this study is that there is a positive and significant relationship between self-efficacy and student engagement. The population is 84 students and the sample is 84 students with total sampling technique. Based on the results of the product moment correlation test, it can be seen that the significance value of the variable self-efficacy and student engagement is <0.001 <0.05. This explains that there is a significant relationship between self-efficacy and student engagement in students. The Pearson correlation value obtained between self-efficacy and student engagement is 0.947. This explains that the self-efficacy variable with student engagement has a positive correlation with a very strong correlation coefficient. The value of the determinant coefficient obtained is equal to 89.7%. Based on the value of the determinant coefficient, it can be seen that the effect of self-efficacy on student engagement is 89.7% and the remaining 10.3% is influenced by other factors.